Subamorphous Thermal Conductivity of Crystalline Half-Heusler Superlattices. Issue 1 (2nd January 2019) - Chavez-Angel, E.; Reuter, N.; Komar, P.; Heinz, S.; Kolb, U.; Kleebe, H.-J.; Jakob, G.
ABSTRACT: The quest to improve the thermoelectric figure of merit has mainly followed the roadmap of lowering the thermal conductivity while keeping unaltered the power factor of the material. Ideally an electron-crystal phonon-glass system is desired. In this work, we report an extraordinary reduction of the cross-plane thermal conductivity in crystalline (TiNiSn):(HfNiSn) half-Heusler superlattices (SLs). We create SLs with thermal conductivities below the effective amorphous limit, which is kept in a large temperature range (120–300 K). We measured thermal conductivity at room temperature values as low as 0.75 W m −1 K −1, the lowest thermal conductivity value reported so far for half-Heusler compounds. By changing the deposition conditions, we also demonstrate that the thermal conductivity is highly impacted by the way the single segments of the SL grow. These findings show a huge potential for thermoelectric generators where an extraordinary reduction of the thermal conductivity is required but without losing the crystal quality of the system